2014
DOI: 10.4168/aair.2014.6.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Immunoglobulin Therapy in Patients With Severe Recalcitrant Atopic Dermatitis: A Preliminary Report

Abstract: The management of severe recalcitrant atopic dermatitis (AD) is a challenging issue for clinicians and patients. We hypothesized that repeated intramuscular injections of autologous immunoglobulin (autologous immunoglobulin therapy: AIGT) might induce clinical improvements in patients with AD by stimulation of the active immune response to antigen-binding-site of pathogenic antibodies. We tried AIGT in 3 adult patients with severe recalcitrant AD whose clinical conditions could not be effectively controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This result suggested that immune dysfunction and hypersensitivity reaction play key roles in the pathogenesis of AD and could be the critical therapeutic targets for AD 3. Further development of a new therapeutic modality is required to change the long-term clinical course of AD 356…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that immune dysfunction and hypersensitivity reaction play key roles in the pathogenesis of AD and could be the critical therapeutic targets for AD 3. Further development of a new therapeutic modality is required to change the long-term clinical course of AD 356…”
Section: Introductionmentioning
confidence: 99%
“…Yu [18] Incomplete or internal inconsistent results in abstract; full article not available Jeon [53] No results related to research questions Sheikhi [54] Insufficient detail in letter to compute effect size or describe design; no further information available Nahm [55] Treatment consisted of autologous immunoglobulin, not whole blood or serum…”
Section: Reason For Exclusionmentioning
confidence: 99%
“…In this study, relatively short-term (12 weeks) changes in clinical severity and laboratory parameters after initiation of AIGT were evaluated. However, further long-term clinical improvements lasting more than 6 months after 4 weeks of AIGT were observed in 2 of 3 patients with severe AD in our previous report [8]. Decreases in peripheral blood eosinophil counts and serum total IgE concentrations could also be observed 6-12 months after initiation of AIGT in the 2 patients with severe AD who showed long-term clinical improvements in that previous report [unpubl.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, autologous immunoglobulin was purified by affinity chromatography using Protein A, and the immunoglobulin isotype used for AIGT was mainly IgG (purity ≥97%) with small amounts of IgM, IgA, and IgE, as reported previously [8,12]. The clinical efficacy and anti-inflammatory properties of polyclonal human IgG purified from multiple healthy blood donors have been reported in various allergic and autoimmune diseases [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation